Model Pelatihan dan Panduan Berkelanjutan untuk Optimalisasi Pemasaran Digital UMKM - Alfitriana, Yesa; Zalianty, Fatikha Nurul; Bahtiar, Zawilla Defitrianti; Izzanda, Aulia Muthiara; Arizan, Ratu; Naraima, Fathia Hafsa; Heydi, Talitha Elvaretta; Agustina, Tri Siwi; Sudarwito, Gurun (Perkumpulan Pendidik Kewirausahaan Indonesia (Perwira Indonesia), 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important contribution in driving inclusive economic growth in Indonesia. However, limited resources, including in the aspects of technology and digital marketing, are still a significant obstacle for many MSMEs, especially those at the micro scale. Batik Wistara, a sociopreneur-based MSME in Surabaya that empowers people with disabilities, faces similar obstacles in optimizing digital marketing. Through a qualitative approach with observation, interview, and documentation methods, mentoring activities were carried out which included digital marketing training, reactivation of social media channels and marketplaces, making product catalogs, and preparing applicable guidebooks. The results showed an increase in business owners' understanding of digital strategies, as well as the formation of a more structured and sustainable marketing system. This activity not only increases the competitiveness of Batik Wistara, but also contributes to inclusive and sustainable development efforts in accordance with the values in the Sustainable Development Goals (SDGs).